Peningkatan Hasil Belajar Seni Budaya Melalui Game PBL Media Ubur-Ubur pada Siswa Kelas VII D di SMPN 10 Malang - Susrivani, Tri Alvianti Putri; Pratamawati, E. W Suprihatin Dyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This analysis is conducted to evaluate the effects of Game PBL (Problem-Based Learning) on Student engagement and learning result in Cultural Arts curriculum for seventh grade students at SMP Negeri 10 Malang. Students at SMP Negeri 10 Malang are still in the process of developing their skills in cultural arts, particularly in the area of traditional dance. Therefore, the implementation of this Game-Based Problem-Based Learning approach is designed to enhance critical thinking and problem-solving abilities through engaging and educational competition. The method used in this study is an experimental design involving pretest and posttest assessments. The findings reveal a significant improvement in students’ learning outcomes, with the average score increasing from 55.1 in the pretest to 78.6 in the posttest—an increase of 23.5 points—after the implementation of the Jellyfish-themed Game PBL. These results indicate that the use of Game PBL with jellyfish media effectively enhances student achievement, while also fostering active engagement and a more contextual understanding of the subject matter.